Comparison of management approaches in deep-seated intracranial arteriovenous malformations: Does treatment improve outcome?. (October 2021) - Patel, Jaimin; Feghali, James; Yang, Wuyang; Rapaport, Sarah; Gami, Abhishek; Sattari, Shahab Aldin; Tamargo, Rafael J.; Caplan, Justin M.; Huang, Judy
Highlights: Benefit from intervention in deep-seated AVMs is questionable. SRS may be the most effective treatment modality when intervention is indicated. Multi-institutional efforts and meta-analyses are needed for guideline development. Abstract: Deep-seated intracranial arteriovenous malformations (AVMs) represent a subset of AVMs characterized by variably reported outcomes regarding the risk of hemorrhage, microsurgical complications, and response to stereotactic radiosurgery (SRS). We aimed to compare outcomes of microsurgery, SRS, endovascular therapy, and conservative follow-up in deep-seated AVMs. A prospectively maintained database of AVM patients (1990–2017) was queried to identify patients with ruptured and unruptured deep-seated AVMs (extension into thalamus, basal ganglia, or brainstem). Comparisons of hemorrhage-free survival and poor functional outcome (modified Rankin scale [mRS] > 2) were performed between conservative management, microsurgery (±pre-procedural embolization), SRS (±pre-procedural embolization), and embolization utilizing multivariable Cox and logistic regression analyses controlling for univariable factors with p < 0.05. Of 789 AVM patients, 102 had deep-seated AVMs (conservative: 34; microsurgery: 6; SRS: 54; embolization: 8). Mean follow-up time was 6.1 years and did not differ significantly between management groups (p = 0.393). Complete obliteration was achieved in 49% of SRS patients. Upon multivariable analysis controlling for baseline rupture with conservative management as a reference group, embolization was associated with an increased hazard of hemorrhage (HR = 6.2, 95%CI [1.1–40.0], p = 0.037), while microsurgery (p = 0.118) and SRS (p = 0.167) provided no significant protection from hemorrhage. Controlling for baseline mRS, microsurgery was associated with an increased risk of poor outcome (OR = 9.2[1.2–68.3], p = 0.030), while SRS (p = 0.557) and embolization (p = 0.541) did not differ significantly from conservative management. Deep AVMs harbor a high risk of hemorrhage, but the benefit from intervention Remains uncertain. SRS may be a relatively more effective approach if interventional therapy is indicated.